Assessing methanol and water leaf extracts of Eriobotraya japonica (Thunb) Lindl for anti-diabetic properties - Sikhakhane, Maria Nomusa (Vaal University of Technology, 2022)
Diabetes mellitus is projected to become one of the world’s leading causes of death and disability in the next 25 years. By 2004, diabetes mellitus was widespread, affecting approximately 25% of the world’s population. Despite developing several drugs, diabetes and its secondary complications remain a major health problem. Many biochemical and chemical agents used to treat hyperglycemia have known side effects. Herbal medicine is used as an alternative form of treatment for diabetes in developing countries where the cost of conventional medicine is still high. This research aimed to assess methanol and water extracts of the leaves Eriobotrya japonica for anti-diabetic properties in vitro. The leaf extracts' bioactive molecules were characterized by thin-layer chromatography (TLC) and Liquid chromatography-mass spectrometry (LC-MS) analysis. The total antioxidant capacity and free radical scavenging activity of the aqueous and methanolic-based extracts were assessed using the DPPH assay. The inhibitory effects of the aqueous and methanolic extracts on alpha-amylase and alpha- glucosidase were examined to evaluate the antidiabetic potential. The qualitative phytochemical analysis showed that pharmacologically active compounds such as tannins, terpenoids, flavonoids, steroids, cardiac glycosides, and phenols were present in the leaves of E. japonica. However, alkaloids were absent in both extracts. The quantitative phytochemical analysis revealed that E. japonica has a lower Total Flavonoids Content (TFC) than Total Phenolic Content (TPC), and this trend was observed in both extracts. The water extract had a TFC of 0.085 ± 0.004 mg of QE/g and TPC of 19.88± 0.2 mg of GAE/g, while the methanol extract had a TFC of 0.084 ± 0.02 mg of QE/g and TPC of 19.10± 0.1 mg of GAE/g. A total of 12 bands were observed on the (TLC) plate of the methanol extract, while none was observed for the water extract. From the (LC-MS), 13 compounds were identified from the water extract of E. japonica. Protocatechuic acid occurred in the highest concentration at 115 mg/L, while Icariside F2; Benzyl beta-D-Apiofuranosyl-(1->6)-O-beta-D-glucopyranoside was found in the lowest concentration of 0.1 mg/L. A total of 14 compounds were characterized from the methanol extract of E. japonica. Blumenin, which belongs to a group of fatty acyl glycosides of mono- and disaccharides, had the highest concentration at 82.7 mg/L, whereas xanthohumol had the lowest concentration at 10.5 mg/L. The 2,2-diphenyl-l-picrylhydrazyl-Thin Layer Chromatography bioautography assay showed that the water extract had 5 bands of compounds with antioxidant activity while the methanol extract showed 6 bands. The free radical scavenging assay was performed using DPPH to qualify antioxidants in E. japanica. The ascorvic acid, methanol, and water extracts had the highest percentage inhibition of 85.9%, and 71.6%, and 40.7%, respectively. The IC50 values for ascorbic acid, methanol, and water extracts were 4.4, 6.1, and 12.2 μg/mL, respectively. Alpha-amylase and alpha-glucosidase activity inhibition assays were performed to determine if E. japonica leaf extracts can slow down the rate at which carbohydrates are digested and absorbed into the blood stream, thus reducing blood sugar levels. The highest concentration of 5 mg/mL of the methanol and the water extracts inhibited 88.5% and 83.01% of alpha-amylase activity, respectively, while acarbose inhibition was at 91.3%. The lowest concentration of 0.0391 mg/mL of the methanol and water extracts inhibited alpha-amylase activity by 40.19% and 22.85%, respectively, while acarbose inhibited the activity by 12.4%. The IC50 values of acarbose, methanol and the water extract were 0.07, 0.03, and 0.06 mg/mL. The highest concentration of 5 mg/mL of the water and the methanol extracts inhibited 72.8% and 77.3% of alpha-glucosidase activity, respectively, while acarbose inhibition was 85.1%. The lowest concentration of 0.0391 mg/mL of the water and methanol extracts inhibited alpha-glucosidase activity by 38.9% and 40.7%, respectively, while acarbose inhibition was 32.0%. The IC50 values of acarbose, methanol and the water extract were 0.03, 0.026, and 0.027 mg/mL. The methanol extract was more potent than the water extract in inhibiting alpha-amylase and alpha-glucosidase activity. The findings from the enzyme activity inhibition assays indicated that E. japonica slows down glucose production and absorption in a dose-dependent manner. Based on the results of this study, it can be concluded that the leaf extracts of E. japonica have bioactive compounds, which can be explored for managing type 2 diabetes.
M. Tech. (Department of Biotechnology, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Eriobotrya japonica; Diabetes mellitus; Phytochemicals; Alpha-amylase; Alpha-glucosidase; Antioxidant; Dissertations, Academic -- South Africa.; Diabetes.; Alternative medicine.